EXPERIENCE TEACHING TO PEDIATRICS STUDENTS OF THE STOMATOLOGICAL FACULTY OF ODESSA INTERNATIONAL HUMANITARIAN UNIVERSITY - Нікітіна, Надія; Беспалова, Алла; Кукушкин, Віталій (Modern engineering and innovative technologies, 2023)
The article presents the results of studying the assessment of teaching pediatrics to students of the Stomatological faculty of the International Humanitarian University. Pediatrics, along with therapy and surgery, is one of the basic disciplines in the f